A Hierarchical Reputation Evidence Decision System in VANETs. (25th October 2015) - Yang, Yang; Gao, Zhipeng; Qiu, Xuesong; Liu, Qian; Hao, Yuwen; Zheng, Jingchen
In VANETs, users are rational, independent, and selfish. Stimulation-based reputation management system is critical for them to avoid selfishness and promote network performance in large-scale VANETs. The current reputation mechanisms produce some problems, for example, overfull energy consumptions, confused collusion, and misreport. In order to detect selfish and collusive behaviors accurately and quickly, we propose a dynamic three-layer reputation evidence decision and management mechanism, which combine with Dempster-Shafer evidence integration mechanism to distinguish selfish nodes. In particular, the system helps in collusion avoidance through reporting falsified reputation evidences of colluders. In addition, we borrow ideas from Weber-Fechner's law and design an adaptive reputation evidence gathering cycle for prolonging the lifetime of detector and overwhelming frequent polling for reputation evidences. The simulation results demonstrate that REDS has higher detection speed for selfish nodes and collusive observers and less network traffic of gathering reputations.